Correction: Determining the geographical origin of milk by multivariate analysis based on stable isotope ratios, elements and fatty acids. Issue 25 (15th June 2021) - Xu, Siyan; Zhao, Chaomin; Deng, Xiaojun; Zhang, Runhe; Qu, Li; Wang, Min; Ren, Shuo; Wu, Hao; Yue, Zhenfeng; Niu, Bing
Abstract : Correction for 'Determining the geographical origin of milk by multivariate analysis based on stable isotope ratios, elements and fatty acids' by Siyan Xu et al., Anal. Methods, 2021, DOI: ; 10.1039/d1ay00339a .